Autistic traits and symptoms of social anxiety are differentially related to attention to others’ eyes in social anxiety disorder - Kleberg, Johan Lundin; Bölte, Sven (Journal of autism and developmental disorders, 2017)
Autism spectrum disorder (ASD) and social anxiety disorder (SAD) have partly overlapping symptoms. Gaze avoidance has been linked to both SAD and ASD, but little is known about differences in social attention between the two conditions. We studied eye movements in a group of treatment-seeking adolescents with SAD (N = 25), assessing SAD and ASD dimensionally. The results indicated a double dissociation between two measures of social attention and the two symptom dimensions. Controlling for social anxiety, elevated autistic traits were associated with delayed orienting to eyes presented among distractors. In contrast, elevated social anxiety levels were associated with faster orienting away from the eyes, when controlling for autistic traits. This distinction deepens our understanding of ASD and SAD.
Gesehen am 27.09.2018
Published online: 20 December 2016